A processing technology for high corrosion-resistant stainless steel strips used in battery casings

By pre-plating the nickel bottom layer and nickel-plated surface layer on the stainless steel strip of the battery shell, and adding specific components to the cleaning solution, combined with nickel-plated graphene, the problem of cracking and unevenness of the battery shell coating during stamping is solved, and the problem of battery shell coating is achieved. High corrosion resistance and wear resistance.

CN115369463BActive Publication Date: 2024-12-13JIANGSU YONGJIN METAL TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202210896226.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-28
Publication Date
2024-12-13
Estimated Expiration
2042-07-28

AI Technical Summary

Technical Problem

The existing battery shell is prone to cracking or falling off during stamping, and the coating is uneven, affecting processing yield and performance.

Method used

Using the secondary nickel plating method, first pre-plating the nickel bottom layer on the surface of the stainless steel strip, then heat treatment, then plating the nickel surface layer after stamping, and citric acid, malic acid and other components are added to the cleaning solution to uniformly coat the nickel layer. , and finally nickel-plated graphene was introduced to improve corrosion resistance and density.

Benefits of technology

It effectively avoids the cracking and peeling of the coating, achieves uniformity and high corrosion resistance of the coating, and improves the surface wear resistance and practicality of the battery case.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a processing technology for a highly corrosion-resistant stainless steel strip for a battery shell. This scheme adopts a secondary nickel plating method to improve it. During processing, a nickel base layer is pre-plated on the surface of the steel strip, and a secondary nickel surface layer is plated on the surface of the steel strip after stamping. The scheme specifies that "the thickness of the nickel base layer is 0.5~1μm, and the thickness of the nickel surface layer is 2~3μm". By limiting the thickness of the nickel base layer, cracking of the coating caused by subsequent stamping is avoided. The present invention discloses a processing technology for a highly corrosion-resistant stainless steel strip for a battery shell. The process design is reasonable and the component ratio is appropriate. The prepared stainless steel battery shell not only has excellent corrosion resistance, but also has excellent surface wear resistance and high practicality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of stainless steel strips, in particular to a processing technology of a high corrosion-resistant stainless steel strip for a battery shell. Background Art

[0002] With the rapid development of my country's automobile industry, electric power industry, railway transportation construction, electronic information industry and other fields, the industry of primary batteries, lead-acid batteries and small secondary batteries in my country's chemical power sources will continue to expand, and the battery casing is one of the more important components.

[0003] There are three main types of battery shell materials currently developed on the market, namely plastic shell, aluminum shell (including aluminum-plastic film) and steel shell. Stainless steel shell has excellent properties such as corrosion resistance and high strength, and has gradually become the main research and development material for battery shells. In actual application, companies have high requirements for the corrosion resistance and surface hardness of stainless steel shells.

[0004] Based on this situation, the present application discloses a processing technology for a highly corrosion-resistant stainless steel strip for a battery casing to solve this technical problem. Summary of the invention

[0005] The object of the present invention is to provide a processing technology for a highly corrosion-resistant stainless steel strip for a battery casing to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A processing technology for a highly corrosion-resistant stainless steel strip for a battery casing comprises the following steps:

[0008] (1) Take the stainless steel strip, place it in an alkaline solution for ultrasonic cleaning for 3 to 5 minutes, take it out and wash it with deionized water, dry it and transfer it to a hydrochloric acid solution for cleaning for 10 to 20 seconds, take it out and wash it with deionized water, dry it and set it aside;

[0009] (2) taking the stainless steel strip cleaned in step (1), soaking it in a cleaning solution for 10 to 20 minutes, taking it out and transferring it to a pre-plating solution for pre-plating a nickel bottom layer, taking it out and washing it with deionized water, and drying it;

[0010] (3) The stainless steel strip cleaned in step (2) is heat treated at 650-680° C. under nitrogen protection for 2-3 h, cooled naturally, and surface smoothed to obtain a finished product.

[0011] In a more optimized solution, the dosage of each component of the cleaning solution is: in mass percentage, 3-5% citric acid, 4-7% malic acid, 0.1-0.3% sodium dodecylbenzene sulfonate, 3-5% thioglycolic acid, 0.05-0.1% 2-mercaptobenzothiazole, 0.1-0.5% tributyl phosphate, and the rest is deionized water.

[0012] In a more optimized solution, in step (2), the amounts of the components of the pre-plating solution are: 25-28 g / L nickel sulfate, 30-32 g / L sodium hypophosphite, 28-32 g / L sodium citrate, 3-5 g / L malic acid, 15-18 g / L sodium acetate, and 0.01-0.03 g / L sodium iodate; the pre-plating temperature is 80-85°C, and the pH of the pre-plating solution is 4.5.

[0013] In a more optimized solution, in step (3), the temperature is raised to 650-680°C at a heating rate of 2-3°C / min during heat treatment.

[0014] The more optimized solution is to take the stainless steel strip prepared in step (3) and perform post-processing, the specific steps of which are:

[0015] (4) Stretching and punching the stainless steel strip into a battery shell to obtain a pre-treated shell; taking the pre-treated shell, cleaning it with a sulfuric acid solution for 5 to 10 seconds, washing it with deionized water, and then soaking it in a cleaning solution for 20 to 40 minutes, taking it out and transferring it to a nickel plating solution for pre-nickel plating, washing it with deionized water, vacuum drying it, and polishing the surface to obtain a finished product.

[0016] In a more optimized solution, in step (4), the amounts of the components of the nickel plating solution are: 23-25 ​​g / L nickel sulfate, 8-10 g / L sodium hypophosphite, 10-12 g / L sodium citrate, 3-5 g / L malic acid, 15-18 g / L sodium acetate, 0.01-0.03 g / L sodium iodate, 3-5 mg / L 2-mercaptobenzothiazole, 1-3 mg / L polyethyleneimine, and 1-2 g / L nickel-plated graphene; the nickel plating temperature is 80-85°C, and the pH of the pre-plating solution is 4.5.

[0017] In a more optimized solution, the thickness of the nickel bottom layer is 0.5-1 μm, and the thickness of the nickel surface layer is 2-3 μm.

[0018] According to a more optimized solution, the preparation steps of the nickel-plated graphene are as follows: taking graphene, activating the surface and placing it in a pre-plating solution for surface nickel plating, and the nickel plating time is 20 to 30 minutes.

[0019] In a more optimized solution, in step (1), the cleaning temperature of the alkali solution is 80-90°C, and the amounts of the components of the alkali solution are: 60-70 g / L of sodium hydroxide, 30-40 g / L of sodium carbonate, 20-30 g / L of trisodium phosphate, and 10-12 g / L of sodium silicate.

[0020] In a more optimized solution, the temperature of the deionized water is 70-80° C., the concentration of the hydrochloric acid solution is 40wt%, and the concentration of the sulfuric acid solution is 5wt%.

[0021] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0022] The invention discloses a processing technology for a high-corrosion-resistant stainless steel strip for a battery shell. In the existing scheme, when preparing the battery shell, generally, nickel or a nickel-cobalt composite layer is pre-plated on the surface of the stainless steel strip, and then the battery shell is prepared by a stretching and stamping method. However, the battery shell needs to undergo multiple deep drawing deformations during the stamping process, so that cracks will appear on the surface coating of the prepared battery shell, and even the coating will fall off, and the overall processing yield will decrease. Therefore, in order to solve the technical problem, the present scheme adopts a secondary nickel plating method to improve it. During processing, a nickel base layer is pre-plated on the surface of the steel strip, and a secondary nickel surface layer is plated on the surface of the steel strip after stamping. In the scheme, it is defined that "the thickness of the nickel base layer is 0.5-1 μm, and the thickness of the nickel surface layer is 2-3 μm". By limiting the thickness of the nickel base layer, cracking of the coating caused by subsequent stamping can be avoided.

[0023] At the same time, after the nickel bottom layer is pre-plated, the scheme performs heat treatment to form an alloy diffusion layer between the plating layer and the steel strip, thereby further improving the bonding strength between the pre-plated nickel layer and the stainless steel strip substrate, so that it will not crack or fall off during the stamping process; after the scheme is stamped into a battery shell, there is a problem in the prior art when nickel plating its surface: after the steel strip is stamped into a battery shell, the nickel plating on its surface is uneven, and the plating thickness is uneven. To improve this situation, the scheme places the pre-treated shell in a sulfuric acid solution for cleaning for 5 to 10 seconds. At this time, the concentration of the sulfuric acid solution is low (5wt%), and the immersion time is short (5 to 10 seconds). The purpose is to The shell surface is cleaned to remove debris and impurities generated during the stamping and stretching process. Short-term cleaning will not have much impact on the coating. Then, it is placed in a cleaning solution containing citric acid, malic acid, sodium dodecylbenzenesulfonate, thioglycolic acid, 2-mercaptobenzothiazole and other components. On the one hand, sulfuric acid is used to clean the surface, and the components of thioglycolic acid and 2-mercaptobenzothiazole can also avoid excessive pickling. On the other hand, after the surface of the steel strip is soaked in the cleaning solution, it is more uniform in the subsequent nickel plating solution, and the residual mercapto groups on its surface can also induce the deposition of nickel, thereby ensuring the uniformity of the subsequent deposition of the nickel layer.

[0024] On the basis of this scheme, the present application also introduces nickel-plated graphene. The reason is that: in the present scheme, there are differences in the component content limits of the pre-plating solution and the nickel-plating solution, wherein the pre-plating solution is a high-phosphorus plating solution, and the nickel-plating solution is a low-phosphorus plating solution. The corrosion resistance of the pre-plating solution coating is relatively excellent, but its hardness and wear resistance are inferior to those of the low-phosphorus plating solution layer. There is a stamping process in the process of the present application. Therefore, in order to avoid the breakage of the coating to the greatest extent, the present scheme uses a high-phosphorus plating solution to plate a nickel bottom layer, giving the stainless steel strip excellent corrosion resistance; uses a low-phosphorus plating solution layer to plate a nickel surface layer, achieving its wear resistance while ensuring the smooth progress of the stamping process; and in order to further improve the corrosion resistance of the nickel surface layer, the scheme introduces nickel-plated graphene, which is doped into the nickel surface layer to improve the density of the coating, thereby ensuring product performance.

[0025] The invention discloses a processing technology for a high corrosion-resistant stainless steel strip for a battery shell. The process design is reasonable and the component ratio is appropriate. The prepared stainless steel battery shell not only has excellent corrosion resistance but also has excellent surface wear resistance and high practicality. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In the following examples, the preparation steps of nickel-plated graphene are as follows: 500 mg of graphene is taken, 500 mL of SnCl is added 2 In the sensitizing solution (SnCl 2 concentration was 0.1 mol / L, HCl concentration was 0.1 mol / L), sensitized at 25°C for 30 min, activated after washing with deionized water, and the activation solution was 00 mL PdCl 2 (PdCl 2 The concentration is 0.001mol / L, the concentration of HCl is 0.25mol / L), activated at 25℃ for 30min, and then the activated graphene is added into the pre-plating solution at a concentration of 1g / L, the nickel plating time is 30min, and then taken out and cleaned for use.

[0028] The stainless steel belt is a 430 stainless steel belt with a thickness of 0.3 mm.

[0029] Embodiment 1:

[0030] A processing technology for a highly corrosion-resistant stainless steel strip for a battery casing comprises the following steps:

[0031] (1) Take a stainless steel strip, place it in an alkali solution for ultrasonic cleaning, the cleaning time is 3 minutes, take it out and wash it with deionized water at 80°C, transfer it to a hydrochloric acid solution after drying, the concentration of the hydrochloric acid solution is 40wt%, wash it for 10 seconds, take it out and wash it with deionized water at 80°C, dry it for use; the cleaning temperature of the alkali solution is 80°C, and the amounts of the components of the alkali solution are: 60g / L sodium hydroxide, 30g / L sodium carbonate, 25g / L trisodium phosphate, and 12g / L sodium silicate.

[0032] (2) Take the stainless steel strip cleaned in step (1), soak it in the cleaning solution for 10 minutes, take it out and transfer it to the pre-plating solution to pre-plating the nickel bottom layer, wash it with 80°C deionized water after the end, and dry it; the thickness of the nickel bottom layer is 1μm. The amount of each component of the pre-plating solution is: 28g / L nickel sulfate, 32g / L sodium hypophosphite, 28g / L sodium citrate, 4g / L malic acid, 16g / L sodium acetate, 0.03g / L sodium iodate; the pre-plating temperature is 80°C, and the pH of the pre-plating solution is 4.5.

[0033] (3) Take the stainless steel strip cleaned in step (2), heat it to 650°C at a heating rate of 3°C / min under nitrogen protection, heat treat it for 3 hours, cool it naturally, and perform surface smoothing treatment.

[0034] (4) The stainless steel strip treated in step (3) is stretched and punched into a battery shell to obtain a pre-treated shell; the pre-treated shell is taken, washed with a sulfuric acid solution with a concentration of 5wt% for 5s, washed with deionized water at 80°C, and then immersed in the cleaning solution for 20min, taken out and transferred to a nickel plating solution for pre-nickel plating, washed with deionized water at 80°C, vacuum dried, and the surface is polished to obtain a finished product. The amount of each component of the nickel plating solution is: nickel sulfate 23g / L, sodium hypophosphite 9g / L, sodium citrate 12g / L, malic acid 5g / L, sodium acetate 16g / L, sodium iodate 0.02g / L, 2-mercaptobenzothiazole 5mg / L, polyethyleneimine 3mg / L, nickel-plated graphene 2g / L; the nickel plating temperature is 80°C, and the pre-plating solution pH is 4.5. The thickness of the nickel surface layer is 3μm.

[0035] In the embodiment, the amounts of the components of the cleaning solution are as follows: by mass percentage, 5% citric acid, 7% malic acid, 0.3% sodium dodecylbenzene sulfonate, 4% thioglycolic acid, 0.1% 2-mercaptobenzothiazole, 0.4% tributyl phosphate, and the rest is deionized water.

[0036] Embodiment 2:

[0037] A processing technology for a highly corrosion-resistant stainless steel strip for a battery casing comprises the following steps:

[0038] (1) Take a stainless steel strip, place it in an alkaline solution for ultrasonic cleaning, the cleaning time is 4 minutes, take it out and wash it with deionized water at 80°C, transfer it to a hydrochloric acid solution after drying, the concentration of the hydrochloric acid solution is 40wt%, wash it for 15 seconds, take it out and wash it with deionized water at 80°C, dry it for use; the cleaning temperature of the alkaline solution is 85°C, and the amounts of the components of the alkaline solution are: 60g / L sodium hydroxide, 30g / L sodium carbonate, 25g / L trisodium phosphate, and 12g / L sodium silicate.

[0039] (2) Take the stainless steel strip cleaned in step (1), soak it in the cleaning solution for 15 minutes, take it out and transfer it to the pre-plating solution to pre-plating the nickel bottom layer, wash it with 80°C deionized water after the end, and dry it; the thickness of the nickel bottom layer is 1μm. The amount of each component of the pre-plating solution is: 28g / L nickel sulfate, 32g / L sodium hypophosphite, 28g / L sodium citrate, 4g / L malic acid, 16g / L sodium acetate, 0.03g / L sodium iodate; the pre-plating temperature is 85°C, and the pH of the pre-plating solution is 4.5.

[0040] (3) Take the stainless steel strip cleaned in step (2), heat it to 660°C at a heating rate of 3°C / min under nitrogen protection, heat treat it for 2.5 h, cool it naturally, and perform surface smoothing treatment.

[0041] (4) The stainless steel strip treated in step (3) is stretched and punched into a battery shell to obtain a pre-treated shell; the pre-treated shell is taken, washed with a sulfuric acid solution with a concentration of 5wt% for 8s, washed with deionized water at 80°C, and then immersed in the cleaning solution for 30min, taken out and transferred to a nickel plating solution for pre-nickel plating, washed with deionized water at 80°C, vacuum dried, and the surface is polished to obtain a finished product. The amount of each component of the nickel plating solution is: nickel sulfate 23g / L, sodium hypophosphite 9g / L, sodium citrate 12g / L, malic acid 5g / L, sodium acetate 16g / L, sodium iodate 0.02g / L, 2-mercaptobenzothiazole 5mg / L, polyethyleneimine 3mg / L, nickel-plated graphene 2g / L; the nickel plating temperature is 85°C, and the pre-plating solution pH is 4.5. The thickness of the nickel surface layer is 3μm.

[0042] In the embodiment, the amounts of the components of the cleaning solution are as follows: by mass percentage, 5% citric acid, 7% malic acid, 0.3% sodium dodecylbenzene sulfonate, 4% thioglycolic acid, 0.1% 2-mercaptobenzothiazole, 0.4% tributyl phosphate, and the rest is deionized water.

[0043] Embodiment 3:

[0044] A processing technology for a highly corrosion-resistant stainless steel strip for a battery casing comprises the following steps:

[0045] (1) Take a stainless steel strip, place it in an alkaline solution for ultrasonic cleaning, the cleaning time is 5 minutes, take it out and wash it with deionized water at 80°C, transfer it to a hydrochloric acid solution after drying, the concentration of the hydrochloric acid solution is 40wt%, wash it for 20 seconds, take it out and wash it with deionized water at 80°C, dry it for use; the cleaning temperature of the alkaline solution is 90°C, and the amounts of the components of the alkaline solution are: 60g / L sodium hydroxide, 30g / L sodium carbonate, 25g / L trisodium phosphate, and 12g / L sodium silicate.

[0046] (2) Take the stainless steel strip cleaned in step (1), soak it in the cleaning solution for 20 minutes, take it out and transfer it to the pre-plating solution to pre-plating the nickel bottom layer, wash it with 80°C deionized water after the end, and dry it; the thickness of the nickel bottom layer is 1μm. The amount of each component of the pre-plating solution is: 28g / L nickel sulfate, 32g / L sodium hypophosphite, 28g / L sodium citrate, 4g / L malic acid, 16g / L sodium acetate, 0.03g / L sodium iodate; the pre-plating temperature is 85°C, and the pH of the pre-plating solution is 4.5.

[0047] (3) Take the stainless steel strip cleaned in step (2), heat it to 680°C at a heating rate of 3°C / min under nitrogen protection, heat treat it for 2 h, cool it naturally, and perform surface smoothing.

[0048] (4) The stainless steel strip treated in step (3) is stretched and punched into a battery shell to obtain a pre-treated shell; the pre-treated shell is taken, washed with a sulfuric acid solution with a concentration of 5wt% for 10s, washed with deionized water at 80°C, and then immersed in the cleaning solution for 40min, taken out and transferred to a nickel plating solution for pre-nickel plating of the surface layer, washed with deionized water at 80°C, vacuum dried, and the surface is polished flat to obtain a finished product. The amount of each component of the nickel plating solution is: nickel sulfate 23g / L, sodium hypophosphite 9g / L, sodium citrate 12g / L, malic acid 5g / L, sodium acetate 16g / L, sodium iodate 0.02g / L, 2-mercaptobenzothiazole 5mg / L, polyethyleneimine 3mg / L, nickel-plated graphene 2g / L; the nickel plating temperature is 85°C, and the pre-plating solution pH is 4.5. The thickness of the nickel surface layer is 3μm.

[0049] In the embodiment, the amounts of the components of the cleaning solution are as follows: by mass percentage, 5% citric acid, 7% malic acid, 0.3% sodium dodecylbenzene sulfonate, 4% thioglycolic acid, 0.1% 2-mercaptobenzothiazole, 0.4% tributyl phosphate, and the rest is deionized water.

[0050] Example 4: In Example 4, a stainless steel strip with a nickel-plated bottom layer was prepared.

[0051] A processing technology for a highly corrosion-resistant stainless steel strip for a battery casing comprises the following steps:

[0052] (1) Take a stainless steel strip, place it in an alkaline solution for ultrasonic cleaning, the cleaning time is 4 minutes, take it out and wash it with deionized water at 80°C, transfer it to a hydrochloric acid solution after drying, the concentration of the hydrochloric acid solution is 40wt%, wash it for 15 seconds, take it out and wash it with deionized water at 80°C, dry it for use; the cleaning temperature of the alkaline solution is 85°C, and the amounts of the components of the alkaline solution are: 60g / L sodium hydroxide, 30g / L sodium carbonate, 25g / L trisodium phosphate, and 12g / L sodium silicate.

[0053] (2) Take the stainless steel strip cleaned in step (1), soak it in the cleaning solution for 15 minutes, take it out and transfer it to the pre-plating solution to pre-plating the nickel bottom layer, wash it with 80°C deionized water after the end, and dry it; the thickness of the nickel bottom layer is 1μm. The amount of each component of the pre-plating solution is: 28g / L nickel sulfate, 32g / L sodium hypophosphite, 28g / L sodium citrate, 4g / L malic acid, 16g / L sodium acetate, 0.03g / L sodium iodate; the pre-plating temperature is 85°C, and the pH of the pre-plating solution is 4.5.

[0054] (3) Take the stainless steel strip cleaned in step (2), heat it to 660°C at a heating rate of 3°C / min under nitrogen protection, heat treat it for 2.5 h, cool it naturally, and perform surface smoothing treatment.

[0055] In the embodiment, the amounts of the components of the cleaning solution are as follows: by mass percentage, 5% citric acid, 7% malic acid, 0.3% sodium dodecylbenzene sulfonate, 4% thioglycolic acid, 0.1% 2-mercaptobenzothiazole, 0.4% tributyl phosphate, and the rest is deionized water.

[0056] Comparative Example 1: Example 2 is used as the control group. In Comparative Example 1, the bottom layer and the surface layer are directly pre-plated with nickel, and then the shell is formed by stamping.

[0057] A processing technology for a highly corrosion-resistant stainless steel strip for a battery casing comprises the following steps:

[0058] (1) Take a stainless steel strip, place it in an alkaline solution for ultrasonic cleaning, the cleaning time is 4 minutes, take it out and wash it with deionized water at 80°C, transfer it to a hydrochloric acid solution after drying, the concentration of the hydrochloric acid solution is 40wt%, wash it for 15 seconds, take it out and wash it with deionized water at 80°C, dry it for use; the cleaning temperature of the alkaline solution is 85°C, and the amounts of the components of the alkaline solution are: 60g / L sodium hydroxide, 30g / L sodium carbonate, 25g / L trisodium phosphate, and 12g / L sodium silicate.

[0059] (2) Take the stainless steel strip cleaned in step (1), soak it in the cleaning solution for 15 minutes, take it out and transfer it to the pre-plating solution to pre-plating the nickel bottom layer, wash it with 80°C deionized water after the end, and dry it; the thickness of the nickel bottom layer is 1μm. The amount of each component of the pre-plating solution is: 28g / L nickel sulfate, 32g / L sodium hypophosphite, 28g / L sodium citrate, 4g / L malic acid, 16g / L sodium acetate, 0.03g / L sodium iodate; the pre-plating temperature is 85°C, and the pH of the pre-plating solution is 4.5.

[0060] (3) The stainless steel strip cleaned in step (2) was cleaned with a 5wt% sulfuric acid solution for 8s, washed with 80°C deionized water, and then soaked in the cleaning solution for 30min. After being taken out, it was transferred to a nickel plating solution for pre-nickel plating, washed with 80°C deionized water, and vacuum dried. The amounts of the components of the nickel plating solution were as follows: 23g / L nickel sulfate, 9g / L sodium hypophosphite, 12g / L sodium citrate, 5g / L malic acid, 16g / L sodium acetate, 0.02g / L sodium iodate, 5mg / L 2-mercaptobenzothiazole, 3mg / L polyethyleneimine, and 2g / L nickel-plated graphene. The nickel plating temperature was 85°C, and the pH of the pre-plating solution was 4.5. The thickness of the nickel surface layer was 3μm.

[0061] (4) Take the stainless steel strip cleaned in step (3), heat it to 660°C at a heating rate of 3°C / min under nitrogen protection, heat treat it for 2.5 hours, cool it naturally, and smooth the surface. Then, stretch and punch the stainless steel strip into a battery shell to obtain a battery shell.

[0062] In the embodiment, the amounts of the components of the cleaning solution are as follows: by mass percentage, 5% citric acid, 7% malic acid, 0.3% sodium dodecylbenzene sulfonate, 4% thioglycolic acid, 0.1% 2-mercaptobenzothiazole, 0.4% tributyl phosphate, and the rest is deionized water.

[0063] Comparative Example 2: Example 2 was used as the control group. No cleaning solution was introduced into Comparative Example 2, and the other steps remained unchanged.

[0064] A processing technology for a highly corrosion-resistant stainless steel strip for a battery casing comprises the following steps:

[0065] (1) Take a stainless steel strip, place it in an alkaline solution for ultrasonic cleaning, the cleaning time is 4 minutes, take it out and wash it with deionized water at 80°C, transfer it to a hydrochloric acid solution after drying, the concentration of the hydrochloric acid solution is 40wt%, wash it for 15 seconds, take it out and wash it with deionized water at 80°C, dry it for use; the cleaning temperature of the alkaline solution is 85°C, and the amounts of the components of the alkaline solution are: 60g / L sodium hydroxide, 30g / L sodium carbonate, 25g / L trisodium phosphate, and 12g / L sodium silicate.

[0066] (2) Take the stainless steel strip cleaned in step (1), place it in a pre-plating solution, and pre-plating a nickel bottom layer. After the pre-plating, take it out and wash it with 80°C deionized water, and dry it; the thickness of the nickel bottom layer is 1 μm. The amount of each component of the pre-plating solution is: 28g / L nickel sulfate, 32g / L sodium hypophosphite, 28g / L sodium citrate, 4g / L malic acid, 16g / L sodium acetate, and 0.03g / L sodium iodate; the pre-plating temperature is 85°C, and the pH of the pre-plating solution is 4.5.

[0067] (3) Take the stainless steel strip cleaned in step (2), heat it to 660°C at a heating rate of 3°C / min under nitrogen protection, heat treat it for 2.5 h, cool it naturally, and perform surface smoothing treatment.

[0068] (4) The stainless steel strip treated in step (3) is stretched and punched into a battery shell to obtain a pre-treated shell; the pre-treated shell is taken, washed with a sulfuric acid solution with a concentration of 5wt% for 8s, washed with deionized water at 80°C, transferred to a nickel plating solution for pre-nickel plating, washed with deionized water at 80°C, vacuum dried, and the surface is polished to obtain a finished product. The amount of each component of the nickel plating solution is: nickel sulfate 23g / L, sodium hypophosphite 9g / L, sodium citrate 12g / L, malic acid 5g / L, sodium acetate 16g / L, sodium iodate 0.02g / L, 2-mercaptobenzothiazole 5mg / L, polyethyleneimine 3mg / L, nickel-plated graphene 2g / L; the nickel plating temperature is 85°C, and the pre-plating solution pH is 4.5. The thickness of the nickel surface layer is 3μm.

[0069] Comparative Example 3: Taking Example 2 as the control group, in Comparative Example 3, both the nickel bottom layer and the nickel surface layer are nickel plated with a pre-plating solution, and the other steps remain unchanged.

[0070] A processing technology for a highly corrosion-resistant stainless steel strip for a battery casing comprises the following steps:

[0071] (1) Take a stainless steel strip, place it in an alkaline solution for ultrasonic cleaning, the cleaning time is 4 minutes, take it out and wash it with deionized water at 80°C, transfer it to a hydrochloric acid solution after drying, the concentration of the hydrochloric acid solution is 40wt%, wash it for 15 seconds, take it out and wash it with deionized water at 80°C, dry it for use; the cleaning temperature of the alkaline solution is 85°C, and the amounts of the components of the alkaline solution are: 60g / L sodium hydroxide, 30g / L sodium carbonate, 25g / L trisodium phosphate, and 12g / L sodium silicate.

[0072] (2) Take the stainless steel strip cleaned in step (1), soak it in the cleaning solution for 15 minutes, take it out and transfer it to the pre-plating solution to pre-plating the nickel bottom layer, wash it with 80°C deionized water after the end, and dry it; the thickness of the nickel bottom layer is 1μm. The amount of each component of the pre-plating solution is: 28g / L nickel sulfate, 32g / L sodium hypophosphite, 28g / L sodium citrate, 4g / L malic acid, 16g / L sodium acetate, 0.03g / L sodium iodate; the pre-plating temperature is 85°C, and the pH of the pre-plating solution is 4.5.

[0073] (3) Take the stainless steel strip cleaned in step (2), heat it to 660°C at a heating rate of 3°C / min under nitrogen protection, heat treat it for 2.5 h, cool it naturally, and perform surface smoothing treatment.

[0074] (4) The stainless steel strip treated in step (3) is stretched and punched into a battery shell to obtain a pre-treated shell; the pre-treated shell is taken, washed with a 5wt% sulfuric acid solution for 8s, washed with 80°C deionized water, and then soaked in the cleaning solution for 30min, taken out and transferred to a nickel plating solution for pre-nickel plating, washed with 80°C deionized water, vacuum dried, and the surface is polished to obtain a finished product. The amount of each component of the nickel plating solution is: 28g / L nickel sulfate, 32g / L sodium hypophosphite, 28g / L sodium citrate, 4g / L malic acid, 16g / L sodium acetate, and 0.03g / L sodium iodate; the nickel plating temperature is 85°C, and the pre-plating solution pH is 4.5. The thickness of the nickel surface layer is 3μm.

[0075] In the embodiment, the amounts of the components of the cleaning solution are as follows: by mass percentage, 5% citric acid, 7% malic acid, 0.3% sodium dodecylbenzene sulfonate, 4% thioglycolic acid, 0.1% 2-mercaptobenzothiazole, 0.4% tributyl phosphate, and the rest is deionized water.

[0076] Comparative Example 4: Example 2 was used as the control group. Nickel-plated graphene was not introduced in Comparative Example 4, and the other steps remained unchanged.

[0077] A processing technology for a highly corrosion-resistant stainless steel strip for a battery casing comprises the following steps:

[0078] (1) Take a stainless steel strip, place it in an alkaline solution for ultrasonic cleaning, the cleaning time is 4 minutes, take it out and wash it with deionized water at 80°C, transfer it to a hydrochloric acid solution after drying, the concentration of the hydrochloric acid solution is 40wt%, wash it for 15 seconds, take it out and wash it with deionized water at 80°C, dry it for use; the cleaning temperature of the alkaline solution is 85°C, and the amounts of the components of the alkaline solution are: 60g / L sodium hydroxide, 30g / L sodium carbonate, 25g / L trisodium phosphate, and 12g / L sodium silicate.

[0079] (2) Take the stainless steel strip cleaned in step (1), soak it in the cleaning solution for 15 minutes, take it out and transfer it to the pre-plating solution to pre-plating the nickel bottom layer, wash it with 80°C deionized water after the end, and dry it; the thickness of the nickel bottom layer is 1μm. The amount of each component of the pre-plating solution is: 28g / L nickel sulfate, 32g / L sodium hypophosphite, 28g / L sodium citrate, 4g / L malic acid, 16g / L sodium acetate, 0.03g / L sodium iodate; the pre-plating temperature is 85°C, and the pH of the pre-plating solution is 4.5.

[0080] (3) Take the stainless steel strip cleaned in step (2), heat it to 660°C at a heating rate of 3°C / min under nitrogen protection, heat treat it for 2.5 h, cool it naturally, and perform surface smoothing treatment.

[0081] (4) The stainless steel strip treated in step (3) is stretched and punched into a battery shell to obtain a pre-treated shell; the pre-treated shell is taken, washed with a sulfuric acid solution with a concentration of 5wt% for 8s, washed with deionized water at 80°C, and then immersed in the cleaning solution for 30min, taken out and transferred to a nickel plating solution for pre-nickel plating, washed with deionized water at 80°C, vacuum dried, and the surface is polished to obtain a finished product. The amount of each component of the nickel plating solution is: nickel sulfate 23g / L, sodium hypophosphite 9g / L, sodium citrate 12g / L, malic acid 5g / L, sodium acetate 16g / L, sodium iodate 0.02g / L, 2-mercaptobenzothiazole 5mg / L, polyethyleneimine 3mg / L; the nickel plating temperature is 85°C, and the pre-plating solution pH is 4.5. The thickness of the nickel surface layer is 3μm.

[0082] In the embodiment, the amounts of the components of the cleaning solution are as follows: by mass percentage, 5% citric acid, 7% malic acid, 0.3% sodium dodecylbenzene sulfonate, 4% thioglycolic acid, 0.1% 2-mercaptobenzothiazole, 0.4% tributyl phosphate, and the rest is deionized water.

[0083] Detection experiment:

[0084] 1. The battery shell was processed according to the common method of Examples 1 to 3 and Comparative Example 1, and the cracking of the surface coating was observed. It can be seen that the battery shells prepared according to Examples 1 to 3 had no obvious cracks on the surface, and the coating was uniform and dense, while the battery shell prepared according to Comparative Example 1 had many cracks on the surface, and the cracks were deeper.

[0085] 2. Take the battery cases prepared in Examples 1 to 3 and Comparative Examples 1 to 4, and test their surface hardness. During the test, take 5 test sites and take the average value. The load is 100 g and the loading time is 20 s. Then perform a neutral salt spray test. The test solution is 5% NaCl solution. The continuous spraying is 3 h and the spraying temperature is 35 ° C. Then, the rating is performed according to the standard disclosed in GB / T6461-2002.

[0086] 3. Take the battery casings prepared in Examples 1 to 3 and Comparative Examples 1 to 4, and soak them in a 1wt% sulfuric acid solution for 7 days. After soaking, wipe the surface dry, weigh it, and then compare it with the mass before soaking to calculate the corrosion weight loss rate. The test is performed 5 times and the average value is taken.

[0087] project Example 1 Example 2 Example 3 Comparative Example 1 Neutral Salt Spray Rating Level 8 Level 8 Level 8 Level 5 Corrosion weight loss rate 0.241% 0.239% 0.241% 0.872% Coating hardness (HV) 591.4 597.6 594.7 / project Comparative Example 2 Comparative Example 3 Comparative Example 4 Neutral Salt Spray Rating Level 6 Level 8 Level 7 Corrosion weight loss 0.579% 0.240% 0.364% Coating hardness (HV) 557.6 497.2 573.4

[0088] Conclusion: The present invention discloses a processing technology for a highly corrosion-resistant stainless steel strip for a battery shell. The process design is reasonable and the component ratio is appropriate. The prepared stainless steel battery shell not only has excellent corrosion resistance, but also has excellent surface wear resistance and high practicality.

[0089] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A processing technology for a highly corrosion-resistant stainless steel strip for a battery casing, characterized in that: The following steps are involved: (1) Take the stainless steel strip, place it in an alkaline solution for ultrasonic cleaning for 3 to 5 minutes, take it out and wash it with deionized water, dry it and transfer it to a hydrochloric acid solution for cleaning for 10 to 20 seconds, take it out and wash it with deionized water, dry it and set it aside; (2) Take the stainless steel strip cleaned in step (1), soak it in a cleaning solution for 10-20 minutes, take it out and transfer it to a pre-plating solution for pre-nickel plating, take it out and wash it with deionized water, and dry it; the amount of each component of the cleaning solution is: in mass percentage, citric acid 3-5%, malic acid 4-7%, sodium dodecylbenzene sulfonate 0.1-0.3%, thioglycolic acid 3-5%, 2-mercaptobenzothiazole 0.05-0.1%, tributyl phosphate 0.1-0.5%, and the rest is deionized water; the amount of each component of the pre-plating solution is: nickel sulfate 25-28g / L, sodium hypophosphite 30-32g / L, sodium citrate 28-32g / L, malic acid 3-5g / L, sodium acetate 15-18g / L, sodium iodate 0.01-0.03g / L; the pre-plating temperature is 80-85°C, and the pH of the pre-plating solution is 4.5; (3) taking the stainless steel strip cleaned in step (2), heat treating it at 650-680° C. under nitrogen protection for 2-3 h, cooling it naturally, and smoothing its surface to obtain a finished product; The stainless steel strip prepared in step (3) is post-processed, and the specific steps are as follows: (4) Stretching and punching the stainless steel strip into a battery shell to obtain a pre-treated shell; taking the pre-treated shell, washing it with a sulfuric acid solution for 5 to 10 seconds, washing it with deionized water, and then soaking it in a cleaning solution for 20 to 40 minutes, taking it out and transferring it to a nickel plating solution to pre-nickel-plated the surface, washing it with deionized water, vacuum drying it, and polishing the surface to obtain a finished product; The dosage of each component of the nickel plating solution is: 23-25 ​​g / L nickel sulfate, 8-10 g / L sodium hypophosphite, 10-12 g / L sodium citrate, 3-5 g / L malic acid, 15-18 g / L sodium acetate, 0.01-0.03 g / L sodium iodate, 3-5 mg / L 2-mercaptobenzothiazole, 1-3 mg / L polyethyleneimine, 1-2 g / L nickel-plated graphene; the nickel plating temperature is 80-85° C., and the pH value of the pre-plating solution is 4.5; the thickness of the nickel bottom layer is 0.5-1 μm, and the thickness of the nickel surface layer is 2-3 μm.

2. The processing technology of the highly corrosion-resistant stainless steel strip for battery casing according to claim 1 is characterized in that: In step (3), the temperature is raised to 650-680°C at a heating rate of 2-3°C / min during heat treatment.

3. The processing technology of the highly corrosion-resistant stainless steel strip for battery casing according to claim 1 is characterized in that: The preparation steps of the nickel-plated graphene are as follows: taking graphene, activating the surface and placing it in a pre-plating solution for surface nickel plating, and the nickel plating time is 20 to 30 minutes.

4. The processing technology of the highly corrosion-resistant stainless steel strip for battery casing according to claim 1 is characterized in that: In step (1), the cleaning temperature of the alkali solution is 80-90°C, and the amounts of the components of the alkali solution are: 60-70 g / L of sodium hydroxide, 30-40 g / L of sodium carbonate, 20-30 g / L of trisodium phosphate, and 10-12 g / L of sodium silicate.

5. The processing technology of the highly corrosion-resistant stainless steel strip for battery casing according to claim 1 is characterized in that: The temperature of the deionized water is 70-80° C., the concentration of the hydrochloric acid solution is 40 wt %, and the concentration of the sulfuric acid solution is 5 wt %.

Citation Information

Patent Citations

  • Method for preparing solid phase micro-extraction fiber by self-assembling graphene coating on metal wire layer by layer

    CN102553553A

  • 4B cold-rolled precise steel strip and manufacturing method thereof

    CN105234171A

  • Battery steel belt, battery steel shell using steel belt and manufacturing method for steel shell

    CN106367789A

  • Post chemical mechanical planarization (CMP) cleaning

    CN110643434A

  • Method and apparatus for electroless plating

    EP0141507A2